Nanometer composite paraffin emulsion plugging agent suitable for coal bed gas drilling
By introducing functionalized rigid nanocores into the nano-paraffin emulsion to form a nano-composite paraffin emulsion sealant, the problems of poor rigidity, insufficient strength and insufficient adsorption capacity in the coalbed methane well in the prior art are solved. Achieve better sealing effect and well wall stability.
Patent Information
- Application Number
- CN202510001116.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2045-01-02
AI Technical Summary
The existing nanoparaffin emulsion sealing agents have poor rigidity, insufficient strength and weak adsorption capacity in coalbed methane wells, resulting in unsatisfactory sealing effect and it is difficult to adapt to the unique characteristics of coal rock formations.
By introducing a functionalized rigid nanocore into the paraffin emulsion, combined with the paraffin flexible shell, a nanocomposite paraffin emulsion sealant is formed. This sealant utilizes the deformation ability of paraffin to squeeze into the micro-cracks and micropores of the formation at low temperatures, and improves the compressive strength of the well wall through the cementation of the functionalized nanocore.
It achieves a better sealing effect in coalbed methane wells, enhances the stability of the well wall, improves the compressive strength and adsorption capacity, and significantly improves the durability and reliability of sealing.
Smart Images

Figure CN119391389A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oilfield chemistry in petroleum drilling engineering, and in particular to a nano-composite paraffin emulsion plugging agent suitable for coal-bed methane drilling. Background Art
[0002] During the drilling process of coalbed methane wells, the stability of the wellbore faces severe challenges due to the development of microcracks in the coal rock formation and the strong brittleness of the formation. During the circulation of drilling fluid, the brittleness of the formation makes it susceptible to external disturbances, causing the wellbore to become unstable or collapse, leading to complex downhole problems such as well leakage and drill stuck. Many existing plugging technologies and materials, especially nano plugging agents, are mainly aimed at brittle shale formations with developed microcracks, while there is relatively little research and application of plugging technologies for coal rock formations. The unique pore structure and brittleness of coal rock make it difficult for conventional shale plugging agents to effectively adapt and be applied to coalbed methane wells.
[0003] Nano paraffin wax emulsion has certain advantages in the process of plugging coalbed methane wells. The low melting point of paraffin wax allows it to fully exert its plugging effect in the low temperature environment of coalbed methane wells, especially under the action of pressure difference, paraffin wax emulsion can deform and squeeze into the micropores and microcracks of coal rock, thereby forming a physical plugging and enhancing the stability of the well wall. This characteristic makes the application of nano paraffin wax emulsion in coalbed methane wells well adaptable. However, paraffin wax emulsion still has certain limitations in its application as a plugging material, such as poor rigidity and insufficient strength, which leads to its unsatisfactory plugging effect under high pressure difference conditions. At the same time, its adsorption capacity between the formation and the formation is weak, which further affects the durability and reliability of the plugging. Summary of the invention
[0004] In order to overcome the problems of insufficient adsorption, weak cementation, and poor adaptability to coal-rock formations of conventional nano paraffin wax emulsion plugging agents, the present invention provides a nano composite paraffin wax emulsion plugging agent suitable for coalbed methane drilling. The nano composite paraffin wax emulsion plugging agent has the characteristics of low temperature adaptability to coalbed methane wells, anti-collapse of coal-rock plugging, low friction, wear resistance, non-toxicity and environmental protection.
[0005] In order to achieve the above object, the present invention provides the following technical solutions: One of the technical solutions of the present invention is a method for preparing a nano-composite paraffin emulsion plugging agent suitable for coalbed methane drilling, comprising the following steps: After the emulsifier and water are evenly mixed to obtain a water phase, the paraffin is melted to obtain an oil phase, and the water phase is added to the oil phase to obtain a nano paraffin emulsion; Mixing the sodium hydroxide solution and the nano-chitin and performing a deacetylation reaction to obtain deacetylated nano-chitin; The silane coupling agent is mixed with the ethanol solution and subjected to a hydrolysis reaction to obtain a silane coupling agent hydrolyzate; Adding the deacetylated nano-chitin into the silane coupling agent hydrolyzate to carry out a hydrothermal reaction to obtain an intermediate product I; Mix water, acrylic acid, acrylamide and dimethyldiallylammonium chloride evenly and adjust the pH to be alkaline to obtain a monomer mixture; Adding the intermediate product I to the monomer mixture, and performing a polymerization reaction under the condition of an initiator to obtain an intermediate product II; The intermediate product II is uniformly mixed with the nano paraffin emulsion and the suspending agent to obtain the nano composite paraffin emulsion plugging agent.
[0006] The second technical solution of the present invention is a nano-composite paraffin emulsion plugging agent suitable for coalbed methane drilling, which is prepared by the above preparation method.
[0007] A third technical solution of the present invention is an application of the above-mentioned nano-composite paraffin emulsion plugging agent suitable for coalbed methane drilling in plugging coalbed methane wells.
[0008] The present invention discloses the following technical effects: Nano paraffin emulsion itself has a certain plugging effect. By utilizing the low melting point characteristics of paraffin, it can match the low temperature characteristics of coalbed methane wells. It can be deformed and squeezed into micropores and microcracks to form plugging under the action of pressure difference, but there are still problems such as poor rigidity, insufficient strength, and insufficient adsorption capacity. The present invention introduces a functionalized rigid nano core, combined with a paraffin flexible shell, to provide a nano-composite paraffin emulsion plugging agent, taking into account deformation ability, adsorption characteristics and rigidity, making up for the shortcomings of nano paraffin emulsion. On the one hand, the nano-composite paraffin emulsion plugging agent can utilize the deformation ability of the paraffin shell to squeeze into the micro-cracks and micro-pores of the formation under the action of pressure difference, and flexibly overlap and accumulate at low temperature to form a tight sealing plugging layer. When the temperature is higher than the melting point of paraffin, the functionalized rigid nano core will also be released, which will play a role in cementing and improving the compressive strength of the surrounding coal and rock. The main raw material of this functionalized rigid nano core is selected from nano chitin, which is natural biomass source, non-toxic and environmentally friendly, has nano size effect, and is conducive to plugging micropores, but the original nano chitin has low solubility in water and limited dispersibility. The present invention exposes part of the amino group through partial deacetylation, which is conducive to increasing the electrostatic repulsion between chitin molecular chains and improving its dispersibility and reactivity; and grafts the branch chain with hydrophilic and strong adsorption functional groups such as carboxyl, amide and cationic ammonium on the partially deacetylated nano chitin through a silane coupling agent to improve the functionality of the rigid nano core; especially the adsorption characteristics, on the one hand, are derived from the physical interaction (such as electrostatic interaction or hydrogen bond interaction) between carboxyl, amide, cationic ammonium and formation rock, and on the other hand, are derived from the chemical interaction between the silanol in the silane coupling agent and the silanol in the formation rock, and the mineral cementation reaction with calcium, magnesium, iron, aluminum and other minerals in the coal rock, which synergistically strengthens the cementation between the plugging agent and the well wall rock, thereby significantly improving the well wall stability of the coal rock formation. At the same time, the amino, carboxyl, amide and cationic ammonium contained in the plugging agent also give it excellent clay hydration inhibition, and have a significant inhibitory effect on mudstone in the coal-slime interlayer or mud mixed in coal gangue. In addition, the nanocomposite paraffin emulsion plugging agent provided by the present invention also has good lubricity, due to its good adsorption characteristics, it can form a lubricating film on the surface of the friction pair, thereby effectively reducing the friction coefficient; it can also use the functionalized rigid nano core to repair micro scratches, thereby reducing wear. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0010] Figure 1This is a particle size distribution diagram of the nanocomposite paraffin emulsion plugging agent prepared in Example 1; Figure 2 This is a particle size distribution diagram of the nanocomposite paraffin emulsion plugging agent prepared in Example 2; Figure 3 This is a particle size distribution diagram of the nanocomposite paraffin emulsion plugging agent prepared in Example 3; Figure 4 This is the particle size distribution diagram of the nano-composite paraffin emulsion plugging agent prepared in Example 4. DETAILED DESCRIPTION
[0011] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0012] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0013] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0014] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0015] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0016] In order to overcome the shortcomings of nano paraffin emulsion, such as poor rigidity, insufficient strength, and weak adsorption capacity between the nano paraffin emulsion and the formation, thereby reducing the plugging effect, the research direction of the present invention is focused on the development of composite nano plugging agents. By introducing rigid materials and nanoparticles with enhanced adsorption and bonding properties into the paraffin emulsion, a composite plugging system is formed to improve the mechanical strength and adsorption and bonding properties of the plugging agent, making it more suitable for the special formation environment of coalbed methane wells, thereby reducing the occurrence of complex situations underground.
[0017] The first aspect of the present invention provides a method for preparing a nano-composite paraffin emulsion plugging agent suitable for coalbed methane drilling, comprising the following steps: After the emulsifier and water are evenly mixed to obtain a water phase, the paraffin is melted to obtain an oil phase, and the water phase is added to the oil phase to obtain a nano paraffin emulsion; Mixing the sodium hydroxide solution and the nano-chitin and performing a deacetylation reaction to obtain deacetylated nano-chitin; The silane coupling agent is mixed with the ethanol solution and subjected to a hydrolysis reaction to obtain a silane coupling agent hydrolyzate; Adding the deacetylated nano-chitin into the silane coupling agent hydrolyzate to carry out a hydrothermal reaction to obtain an intermediate product I; Mix water, acrylic acid, acrylamide and dimethyldiallylammonium chloride evenly and adjust the pH to be alkaline to obtain a monomer mixture; Adding the intermediate product I to the monomer mixture, and performing a polymerization reaction under the condition of an initiator to obtain an intermediate product II; The intermediate product II is uniformly mixed with the nano paraffin emulsion and the suspending agent to obtain the nano composite paraffin emulsion plugging agent.
[0018] In some embodiments of the present invention, after the emulsifier and water are evenly mixed, an aqueous phase is obtained, specifically: after the emulsifier and water are mixed, the mixture is stirred at 55-65° C. for 30-60 min to ensure that the emulsifier and water are fully mixed. In the present invention, the aqueous phase is added to the oil phase to obtain a nano paraffin emulsion, specifically: under stirring conditions, the aqueous phase is slowly added to the oil phase, and stirring is continued at 80-90° C. for 10-20 min to obtain a nano paraffin emulsion.
[0019] In some embodiments of the present invention, the emulsifier is a mixture of Span and Tween; the mass ratio of the emulsifier, water, and paraffin is (20-30): (120-140): (30-60).
[0020] In some embodiments of the present invention, the emulsifier is a mixture of Span 40 and Tween 21 in a mass ratio of 1:1 (HLB=10.0), a mixture of Span 60 and Tween 40 in a mass ratio of 1:1 (HLB=10.2), or a mixture of Span 65 and Tween 20 in a mass ratio of 45:55 (HLB=10.1); the paraffin is 52# paraffin, 54# paraffin, 56# paraffin, 58# paraffin, 60# paraffin or 62# paraffin.
[0021] In some embodiments of the present invention, a sodium hydroxide solution and nano-chitin are mixed and then subjected to a deacetylation reaction to obtain deacetylated nano-chitin, specifically: nano-chitin is mixed with a sodium hydroxide solution, and then subjected to a deacetylation reaction at 85-95° C., reacted for 1-2 hours, cooled to room temperature, and subjected to centrifugation, deionized water washing, ethanol dehydration and freeze drying to obtain deacetylated nano-chitin; the mass concentration of the sodium hydroxide solution is 30%-40%; the mass ratio of the nano-chitin, the sodium hydroxide solution and the paraffin is (10-20): (100-150): (30-60).
[0022] In the application of drilling fluid plugging agent, the complete deacetylation of chitin not only has a long reaction time and high cost, but also causes the crystallinity to decrease and the hydrogen bonding between molecular chains to weaken, weakens the strength of the plugging layer, is difficult to resist the high pressure difference in the well wall crack, and finally reduces the plugging effect. Therefore, the present invention, by limiting the mass ratio of reaction temperature, time, sodium hydroxide solution concentration and nano-chitin and sodium hydroxide solution, makes nano-chitin undergo partial deacetylation reaction, promotes partial amino exposure on its molecular chain, increases the electrostatic repulsion between molecules, improves the dispersibility of the material, and improves the reactivity and stability. Meanwhile, the retained partial acetyl structure gives the material appropriate crystallinity and rigidity, thereby forming a plugging layer with higher strength and better stability, which is conducive to the stability of the coal seam well wall.
[0023] In some embodiments of the present invention, the average particle size of the nano-chitosan is 10-50 nm.
[0024] In some embodiments of the present invention, the silane coupling agent is vinyl triethoxysilane, dimethyl vinyl ethoxysilane or vinyl tri (2-methoxyethoxy) silane; the mass ratio of the silane coupling agent to the paraffin is (3-5): (30-60); the mass fraction of the ethanol solution is 90%; the temperature of the hydrolysis reaction is 50-60°C, and the time is 3-5h.
[0025] In some embodiments of the present invention, the temperature of the hydrothermal reaction is 70-80°C and the time is 16-20 hours. After the hydrothermal reaction is completed, the reaction system is cooled to room temperature, the precipitate is collected by centrifugation, and the precipitate is washed and dried.
[0026] In some embodiments of the present invention, the mass ratio of paraffin wax, acrylic acid, acrylamide and dimethyldiallyl ammonium chloride is (30-60): (3-5): (2-4): (5-10); when water, acrylic acid, acrylamide and dimethyldiallyl ammonium chloride are uniformly mixed, the mass ratio of water to acrylic acid used is 100: (3-5); the pH is 7-8. The present invention has no special requirements for the alkali solution used to adjust the pH, and conventional technical means of those skilled in the art can be selected, for example: 0.1 mol / L NaOH solution.
[0027] In some embodiments of the present invention, the intermediate product I is added to the monomer mixture, and a polymerization reaction is carried out under initiator conditions, specifically: the intermediate product I is added to the monomer mixture under stirring conditions, nitrogen is passed to deoxygenate, the temperature is raised to 70-80° C., and an initiator is added to initiate the polymerization reaction, which is continued for 2-3 hours; after the polymerization reaction is completed, the reaction system is cooled to room temperature, the precipitate is collected by centrifugation, the precipitant is washed, vacuum dried and ground.
[0028] In some embodiments of the present invention, the initiator is potassium persulfate and / or ammonium persulfate; the mass ratio of the initiator to the acrylic acid is (0.1-0.3): (3-5).
[0029] In some embodiments of the present invention, the suspending agent is a mixture of 40-60 parts of xanthan gum, 20-30 parts of guar gum and 20-30 parts of alginate, and the mass ratio of the suspending agent to the paraffin is (0.10-0.16): (30-60). Xanthan gum, guar gum and alginate are all biopolysaccharide polymers, have good low-temperature water solubility and suspension stability, and can improve the anti-sedimentation stability of the nanocomposite paraffin emulsion plugging agent.
[0030] The second aspect of the present invention provides a nano-composite paraffin emulsion plugging agent suitable for coalbed methane drilling and prepared by the above-mentioned preparation method.
[0031] The nano-composite paraffin emulsion plugging agent provided by the present invention has a particle size range of 45-737nm, has a wide distribution on the nanoscale, can achieve the plugging of nano-pores or cracks step by step through particle size matching, also has significant anti-collapse, inhibition and lubrication properties, and is friendly to the ecological environment.
[0032] The third aspect of the present invention provides an application of the nano-composite paraffin emulsion plugging agent suitable for coalbed methane drilling in plugging coalbed methane wells.
[0033] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.
[0034] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0035] In the examples, "parts" means "parts by mass". Example 1
[0036] A nano-composite paraffin emulsion plugging agent suitable for coalbed methane drilling, the preparation method thereof has the following steps: 1. Add 120 parts of deionized water and 20 parts of emulsifier (a mixture of Span 40 and Tween 21 in a mass ratio of 1:1 (HLB=10.0)) into a beaker, place it on a magnetic heating stirrer and heat it to 55°C, stir it for 30 minutes to obtain a water phase; then add 30 parts of 52# paraffin wax into a three-necked flask, heat it in a water bath to 65°C, stir it for 10 minutes to obtain an oil phase; then, under stirring, slowly add the water phase into the three-necked flask containing the oil phase, raise the temperature to 80°C, and continue stirring for 10 minutes to obtain a nano paraffin wax emulsion; 2. Add 10 parts of nano-chitin (average particle size of 10 nm) into a polytetrafluoroethylene beaker containing 100 parts of 30% sodium hydroxide solution by mass, place it on a magnetic heating stirrer and heat it to 85°C for partial deacetylation reaction. After reacting for 1 hour, cool it to room temperature, and obtain partially deacetylated nano-chitin after centrifugation, deionized water washing, ethanol dehydration and freeze drying; 3. Add 3 parts of vinyl triethoxysilane and 150 parts of 90% ethanol solution by mass into a four-necked flask, slowly heat to 50°C under stirring, and hydrolyze for 3 hours to obtain a silane coupling agent hydrolyzate; then slowly add the partially deacetylated nano-chitin prepared in step 2, continue stirring and heat to 70°C, stop heating after reacting for 16 hours, and cool to room temperature; obtain the precipitate by centrifugation, wash it with anhydrous ethanol, and then vacuum dry it to obtain intermediate product I; 4. Add 100 parts of deionized water, 3 parts of acrylic acid, 2 parts of acrylamide and 5 parts of dimethyldiallylammonium chloride into another four-necked flask, and adjust the pH to 7 with 0.1 mol / L NaOH solution, stir for 20 minutes, and obtain a monomer mixture; then add intermediate product I thereto under stirring, pass nitrogen to deoxygenate, heat to 70°C, and add 0.1 parts of potassium persulfate to initiate polymerization, continue for 2 hours, cool to room temperature, centrifuge, wash, vacuum dry and grind to obtain intermediate product II; 5. During the stirring process, the intermediate product II was slowly added into the three-necked flask containing the nano paraffin emulsion, and then 0.10 parts of the suspending agent was added. After stirring for 30 minutes, the nano composite paraffin emulsion plugging agent was obtained.
[0037] Wherein, the suspending agent is a mixture of 40 parts of xanthan gum, 20 parts of guar gum and 20 parts of alginate, calculated by mass.
[0038] The particle size distribution of the nanocomposite paraffin emulsion plugging agent prepared in this example is as follows: Figure 1 As shown, the particle size range is 45~622nm, and the average particle size is 195nm. Example 2
[0039] A nano-composite paraffin emulsion plugging agent suitable for coalbed methane drilling, the preparation method thereof has the following steps: 1. Add 140 parts of deionized water and 30 parts of emulsifier (a mixture of Span 60 and Tween 40 in a mass ratio of 1:1 (HLB=10.2)) into a beaker, place it on a magnetic heating stirrer and heat it to 65°C, stir it for 60 minutes to obtain a water phase; then add 60 parts of 62# paraffin wax into a three-necked flask, heat it to 75°C in a water bath, stir it for 20 minutes to obtain an oil phase; then, under stirring, slowly add the water phase into the three-necked flask containing the oil phase, raise the temperature to 90°C, and continue stirring for 20 minutes to obtain a nano paraffin wax emulsion; 2. Add 20 parts of nano-chitin (average particle size of 50 nm) into a polytetrafluoroethylene beaker containing 150 parts of 40% sodium hydroxide solution by mass, place it on a magnetic heating stirrer and heat it to 95°C for partial deacetylation reaction. After reacting for 2 hours, cool it to room temperature, and obtain partially deacetylated nano-chitin after centrifugation, deionized water washing, ethanol dehydration and freeze drying; 3. Add 5 parts of vinyl tris (2-methoxyethoxy) silane and 200 parts of 90% ethanol solution by mass into a four-necked flask, slowly heat to 60°C under stirring, and hydrolyze for 5 hours to obtain a silane coupling agent hydrolyzate; then slowly add the partially deacetylated nano-chitin prepared in step 2, continue stirring and heat to 80°C, stop heating after reacting for 20 hours, and cool to room temperature; obtain the precipitate by centrifugation, wash it with anhydrous ethanol, and then vacuum dry it to obtain the intermediate product I; 4. Add 100 parts of deionized water, 5 parts of acrylic acid, 4 parts of acrylamide and 10 parts of dimethyldiallylammonium chloride into another four-necked flask, and adjust the pH to 8 with 0.1 mol / L NaOH solution, stir for 30 minutes, and obtain a monomer mixture; then add intermediate product I thereto under stirring, pass nitrogen to deoxygenate, heat to 80° C., and add 0.3 parts of ammonium persulfate to initiate polymerization, continue for 3 hours, cool to room temperature, centrifuge, wash, vacuum dry and grind to obtain intermediate product II; 5. During the stirring process, the intermediate product II was slowly added into the three-necked flask containing the nano paraffin emulsion, and then 0.16 parts of the suspending agent was added. After stirring for 60 minutes, the nano composite paraffin emulsion plugging agent was obtained.
[0040] Wherein, the suspending agent is a mixture of 60 parts of xanthan gum, 20 parts of guar gum and 20 parts of alginate, calculated by mass.
[0041] The particle size distribution of the nanocomposite paraffin emulsion plugging agent prepared in this example is as follows: Figure 2 As shown, the particle size range is 65~705nm and the average particle size is 344nm. Example 3
[0042] A nano-composite paraffin emulsion plugging agent suitable for coalbed methane drilling, the preparation method thereof has the following steps: 1. Add 130 parts of deionized water and 25 parts of emulsifier (a mixture of Span 65 and Tween 20 in a mass ratio of 45:55 (HLB=10.1)) into a beaker, place it on a magnetic heating stirrer and heat it to 60°C, stir it for 45 minutes to obtain a water phase; then add 45 parts of 56# paraffin wax into a three-necked flask, heat it in a water bath to 70°C, stir it for 15 minutes to obtain an oil phase; then, under stirring, slowly add the water phase into the three-necked flask containing the oil phase, raise the temperature to 85°C, and continue stirring for 15 minutes to obtain a nano paraffin wax emulsion; 2. Add 15 parts of nano-chitin (average particle size of 30 nm) into a polytetrafluoroethylene beaker containing 125 parts of 35% sodium hydroxide solution by mass, place it on a magnetic heating stirrer and heat it to 90°C for partial deacetylation reaction. After reacting for 1.5 hours, cool it to room temperature, and obtain partially deacetylated nano-chitin after centrifugation, deionized water washing, ethanol dehydration and freeze drying; 3. Add 4 parts of dimethylvinylethoxysilane and 175 parts of 90% ethanol solution by mass into a four-necked flask, slowly heat to 55°C under stirring, and hydrolyze for 4 hours to obtain a silane coupling agent hydrolyzate; then slowly add the partially deacetylated nano-chitin prepared in step 2, continue stirring and heat to 75°C, stop heating after 18 hours of reaction, and cool to room temperature; obtain the precipitate by centrifugation, wash it with anhydrous ethanol, and then vacuum dry it to obtain the intermediate product I; 4. Add 100 parts of deionized water, 4 parts of acrylic acid, 3 parts of acrylamide and 7.5 parts of dimethyldiallylammonium chloride into another four-necked flask, and adjust the pH to 7.5 with 0.1 mol / L NaOH solution, stir for 25 minutes, and obtain a monomer mixture; then add intermediate product I thereto under stirring, pass nitrogen to deoxygenate, heat to 75°C, and add 0.2 parts of initiator to initiate polymerization reaction, continue for 2.5 hours, cool to room temperature, centrifuge, wash, vacuum dry and grind to obtain intermediate product II; 5. During the stirring process, the intermediate product II was slowly added into the three-necked flask containing the nano paraffin emulsion, and then 0.13 parts of the suspending agent was added. After stirring for 45 minutes, the nano composite paraffin emulsion plugging agent was obtained.
[0043] Wherein, the initiator is a mixture of 50 parts of potassium persulfate and 50 parts of ammonium persulfate by mass; The suspending agent is a mixture of 50 parts of xanthan gum, 25 parts of guar gum and 25 parts of alginate by weight.
[0044] The particle size distribution of the nanocomposite paraffin emulsion plugging agent prepared in this example is as follows: Figure 3 As shown, the particle size ranges from 54 to 737 nm, and the average particle size is 323 nm. Example 4
[0045] A nano-composite paraffin emulsion plugging agent suitable for coalbed methane drilling, the preparation method thereof has the following steps: 1. Add 140 parts of deionized water and 20 parts of emulsifier (a mixture of Span 60 and Tween 40 in a mass ratio of 1:1 (HLB=10.2)) into a beaker, place it on a magnetic heating stirrer and heat it to 62°C, stir it for 50 minutes to obtain a water phase; then add 45 parts of 58# paraffin into a three-necked flask, heat it in a water bath to 68°C, stir it for 16 minutes to obtain an oil phase; then, under stirring, slowly add the water phase into the three-necked flask containing the oil phase, raise the temperature to 88°C, and continue stirring for 17 minutes to obtain a nano paraffin emulsion; 2. Add 16 parts of nano-chitin (average particle size of 20 nm) into a polytetrafluoroethylene beaker containing 120 parts of 33% sodium hydroxide solution by mass, place it on a magnetic heating stirrer and heat it to 93°C for partial deacetylation reaction. After reacting for 1.3 hours, cool it to room temperature, and obtain partially deacetylated nano-chitin after centrifugation, deionized water washing, ethanol dehydration and freeze drying; 3. Add 3 parts of vinyl triethoxysilane and 160 parts of 90% ethanol solution by mass into a four-necked flask, slowly heat to 56°C under stirring, and hydrolyze for 3.5 hours to obtain a silane coupling agent hydrolyzate; then slowly add the partially deacetylated nano-chitin prepared in step 2, continue stirring and heat to 77°C, stop heating after 18 hours of reaction, and cool to room temperature; obtain the precipitate by centrifugation, wash with anhydrous ethanol, and then vacuum dry to obtain intermediate product I; 4. Add 100 parts of deionized water, 5 parts of acrylic acid, 3 parts of acrylamide and 8 parts of dimethyldiallylammonium chloride into another four-necked flask, and adjust the pH to 8 with 0.1 mol / L NaOH solution, stir for 28 minutes, and obtain a monomer mixture; then add intermediate product I thereto under stirring, pass nitrogen to deoxygenate, heat to 73° C., and add 0.15 parts of initiator to initiate polymerization reaction, continue for 3 hours, cool to room temperature, centrifuge, wash, vacuum dry and grind to obtain intermediate product II; 5. During the stirring process, the intermediate product II was slowly added into the three-necked flask containing the nano paraffin emulsion, and then 0.15 parts of the suspending agent was added. After stirring for 40 minutes, the nano composite paraffin emulsion plugging agent was obtained.
[0046] Wherein, the initiator is a mixture of 30 parts of potassium persulfate and 70 parts of ammonium persulfate by mass; The suspending agent is a mixture of 45 parts of xanthan gum, 30 parts of guar gum and 25 parts of alginate by weight.
[0047] The particle size distribution of the nanocomposite paraffin emulsion plugging agent prepared in this example is as follows: Figure 4 As shown, the particle size ranges from 52 to 567 nm, and the average particle size is 234 nm. Comparative Example 1
[0048] 130 parts of deionized water and 25 parts of emulsifier (a mixture of Span 65 and Tween 20 in a mass ratio of 45:55 (HLB=10.1)) were added to a beaker, placed on a magnetic heating stirrer and heated to 60°C, stirred for 45 minutes to obtain a water phase; 45 parts of 56# paraffin were added to a three-necked flask, heated to 70°C in a water bath, stirred for 15 minutes to obtain an oil phase; then, under stirring, the water phase was slowly added to the three-necked flask containing the oil phase, the temperature was raised to 85°C, and stirring was continued for 15 minutes to obtain a nano paraffin emulsion. (That is, the nano paraffin emulsion provided in this comparative example is the nano paraffin emulsion prepared in step 1 of Example 3) Effect verification: The nanocomposite paraffin emulsion plugging agents obtained in the above Examples 1-4 and the nanoparaffin emulsion obtained in Comparative Example 1 were added to the following drilling fluids for performance evaluation. The performance tests were carried out according to the test methods in GB / T16783.1-2014 "Field Test of Drilling Fluids in Petroleum and Natural Gas Industry Part 1: Water-Based Drilling Fluids", GB / T 29170-2012 "Laboratory Test of Drilling Fluids in Petroleum and Natural Gas Industry" and SY / T 7467-2020 "Technical Specifications for Environmental Performance Evaluation of Drilling Fluids". The results are shown in Tables 1 to 3 (in Tables 1 to 3, "%" represents the mass percentage of the plugging agent added in the embodiment or comparative example to the drilling fluid).
[0049] Drilling fluid formula: fresh water + 3% bentonite + 0.3% sodium hydroxide + 0.3% sodium carbonate + 5% potassium chloride + 0.3% zwitterionic polymer strong coating agent + 0.3% high viscosity carboxymethyl cellulose + 3% lignite resin + barite weighted to a density of 1.20g / cm 3 .
[0050] Table 1 Effect of nanocomposite paraffin wax emulsion plugging agent on rheological properties of drilling fluid , Table 2 Effect of nanocomposite paraffin emulsion plugging agent on the plugging and anti-collapse performance of drilling fluid , Table 3 Effect of nanocomposite paraffin wax emulsion plugging agent on the lubrication performance of drilling fluid , Note: T: aging temperature of base slurry or drilling fluid, °C t: Drilling fluid rolling aging time, h PV: drilling fluid plastic viscosity, mPa·s YP: Drilling fluid dynamic shear force, Pa API: Drilling fluid medium pressure loss (0.7MPa, room temperature, 30min), mL HTHP: Drilling fluid high temperature and high pressure filtration loss (3.5MPa, T, 30min), mL CF: extreme pressure friction coefficient, dimensionless ΔCF: Extreme pressure friction coefficient reduction rate, % δ: HTHP mud cake thickness (3.5MPa, T, 30min), mm θ: HTHP mud cake clear water loss (3.5MPa, T, 30min), mL η: Coal rock strength retention rate (3.5MPa, T, 72h), % γ: Mudstone expansion rate, % It can be seen from the data of Examples 1 to 4 and Comparative Example 1 in Table 1 that 1% nano-composite paraffin wax emulsion plugging agent has little effect on the rheology of the drilling fluid. When the amount is increased to 3%, the viscosity of the drilling fluid increases slightly, but the overall change is small; the nano-paraffin wax emulsion has little effect on the rheology of the drilling fluid, but due to the increase in the liquid phase content, the viscosity of the drilling fluid shows a downward trend. In comparison, the functionalized nano-chitin core contained in the nano-composite paraffin wax emulsion plugging agent makes up for this part of the viscosity loss.
[0051] From the data of Examples 1 to 4 and Comparative Example 1 in Table 2, it can be seen that the blank drilling fluid filtration is too large, the mud cake is too thick, the mud cake clear water filtration is large, the density is insufficient, and there is almost no strengthening effect on the coal rock, the anti-collapse property is poor, and the mudstone expansion rate is too large, and the inhibition is insufficient; while the 1% nano-composite paraffin emulsion plugging agent has a significant filtration reduction effect, and the mud cake thickness and the mud cake clear water filtration loss are significantly reduced, indicating that the mud cake density is improved, and at the same time, it plays a cementing role on the coal rock, the strength is significantly improved, and the inhibition is strengthened, the mudstone expansion The expansion rate is significantly reduced; when the addition amount is increased to 3%, all aspects of performance are further improved, the API and HTHP filtration loss reduction rates are both greater than 50%, the HTHP mud cake thickness reduction rate is greater than 45%, the HTHP mud cake clear water filtration loss reduction rate is greater than 65%, the coal rock strength retention rate is greater than 35%, the mudstone expansion reduction rate is greater than 70%, and the plugging, anti-collapse and inhibition effects are significant; in contrast, the nano paraffin emulsion has little improvement on the plugging and inhibition performance of the drilling fluid, and has almost no improvement in improving the coal rock strength, and the anti-collapse effect is not good.
[0052] From the data of Examples 1 to 4 and Comparative Example 1 in Table 3, it can be seen that the extreme pressure friction coefficient of the blank drilling fluid is relatively large and the lubricity is poor; the addition of the nano-composite paraffin emulsion plugging agent can significantly reduce the friction coefficient and improve the lubricity; although the nano-paraffin emulsion also has the ability to improve lubrication, the effect is obviously inferior to that of the nano-composite paraffin emulsion plugging agent at the same addition amount.
[0053] In summary, the nano-composite paraffin emulsion plugging agent suitable for coalbed methane drilling of the present invention has remarkable effects in plugging, anti-collapse, inhibition and lubrication, which is beneficial to stabilizing the coal and rock well wall and ensuring safe and efficient drilling operations of coalbed methane wells.
[0054] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a nanocomposite paraffin emulsion plugging agent suitable for coalbed methane drilling, characterized in that: The following steps are involved: After the emulsifier and water are evenly mixed to obtain a water phase, the paraffin is melted to obtain an oil phase, and the water phase is added to the oil phase to obtain a nano paraffin emulsion; The sodium hydroxide solution and the nano-chitin are mixed and then subjected to a deacetylation reaction to obtain deacetylated nano-chitin; The silane coupling agent is mixed with the ethanol solution and subjected to a hydrolysis reaction to obtain a silane coupling agent hydrolyzate; Adding the deacetylated nano-chitin into the silane coupling agent hydrolyzate to carry out a hydrothermal reaction to obtain an intermediate product I; Mix water, acrylic acid, acrylamide and dimethyldiallylammonium chloride evenly and adjust the pH to be alkaline to obtain a monomer mixture; Adding the intermediate product I to the monomer mixture, and performing a polymerization reaction under initiator conditions to obtain an intermediate product II; The intermediate product II is uniformly mixed with the nano paraffin emulsion and the suspending agent to obtain the nano composite paraffin emulsion plugging agent.
2. The method for preparing the nano-composite paraffin emulsion plugging agent suitable for coalbed methane drilling according to claim 1, characterized in that: The emulsifier is a mixture of Span and Tween; the mass ratio of the emulsifier, water and paraffin is (20-30): (120-140): (30-60).
3. The method for preparing the nano-composite paraffin emulsion plugging agent suitable for coalbed methane drilling according to claim 1, characterized in that: The mass concentration of the sodium hydroxide solution is 30%-40%; the mass ratio of the nano-chitin, the sodium hydroxide solution and the paraffin is (10-20): (100-150): (30-60); the reaction temperature of the deacetylation reaction is 85-95° C., and the reaction time is 1-2 hours.
4. The method for preparing the nano-composite paraffin emulsion plugging agent suitable for coalbed methane drilling according to claim 1, characterized in that: The silane coupling agent is vinyl triethoxysilane, dimethyl vinyl ethoxysilane or vinyl tri (2-methoxyethoxy) silane; the mass ratio of the silane coupling agent to the paraffin is (3-5): (30-60); the temperature of the hydrolysis reaction is 50-60°C, and the time is 3-5h.
5. The method for preparing the nano-composite paraffin emulsion plugging agent suitable for coalbed methane drilling according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 70-80° C. and the time is 16-20 hours.
6. The method for preparing the nano-composite paraffin emulsion plugging agent suitable for coalbed methane drilling according to claim 1, characterized in that: The mass ratio of the paraffin wax, acrylic acid, acrylamide and dimethyldiallylammonium chloride is (30-60): (3-5): (2-4): (5-10); and the pH is 7-8.
7. The method for preparing the nano-composite paraffin emulsion plugging agent suitable for coalbed methane drilling according to claim 1, characterized in that: The initiator is potassium persulfate and / or ammonium persulfate; the polymerization reaction temperature is 70-80° C. and the reaction time is 2-3 hours.
8. The method for preparing the nano-composite paraffin emulsion plugging agent suitable for coalbed methane drilling according to claim 1, characterized in that: In terms of weight, the suspending agent is a mixture of 40-60 parts of xanthan gum, 20-30 parts of guar gum and 20-30 parts of alginate; the mass ratio of the suspending agent to the paraffin is (0.10-0.16): (30-60).
9. A nanocomposite paraffin emulsion plugging agent suitable for coalbed methane drilling, prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the nano-composite paraffin emulsion plugging agent suitable for coal-bed methane drilling as claimed in claim 9 in plugging coal-bed methane wells.
Citation Information
Patent Citations
Environment-friendly plugging agent for drilling fluid based on modified basalt fiber powder, and preparation method thereof
CN113549432A
Polymer clean drilling fluid system
CN113897187A
Bionic and amphiphobic high-efficiency water-based drilling fluid
CN114350332A
High-temperature-resistant chemical wall fixing agent for drilling fluid for stabilizing gravel layer well wall as well as preparation method and application of high-temperature-resistant chemical wall fixing agent
CN114591718A
Lubricating and plugging filtrate reducer for drilling fluid and preparation method of lubricating and plugging filtrate reducer
CN114686183A